Sucrose addition directionally enhances bacterial community convergence and network stability of the shrimp culture system - Guo, Haipeng; Dong, Pengsheng; Gao, Fan; Huang, Lei; Wang, Sipeng; Wang, Ruoyu; Yan, Mengchen; Zhang, Demin (NPJ biofilms and microbiomes, 2022)
Sucrose is an effective carbon source for creating more reliable and environmentally friendly conditions for shrimp growth by regulating bacteria in biofloc-based culture systems. However, the influence of sucrose addition on the interaction, co-occurrence networks, and assembly mechanisms of bacterial communities in biofloc-based culture systems remains largely unknown. Here, we comprehensively investigated the effects of sucrose addition on bacterial communities in three habitats (water, bioflocs, and gut). The bacterial community structures and compositions of these three habitats became more similar in groups with sucrose addition, compared with those in controls. More than 50% gut bacterial communities were mainly derived from water and biofloc communities in the sucrose addition groups, but only about 33% bacterial communities migrated from water and biofloc to the gut in the control culture system. Sucrose addition accordantly enriched core taxa belonging to the phylum Actinobacteria and the families Rhodobacteraceae and Flavobacteriaceae in water, biofloc, and gut habitats. These core taxa were important for maintaining bacterial network stability in the sucrose addition culture systems and some were identified as keystone taxa for improving shrimp growth. Furthermore, after sucrose addition, gut bacterial community assembly from water and biofloc was dominated by the heterogeneous select with the ratios of 55–91% and 67–83%, respectively, indicating that sucrose addition can directionally shape the bacterial assembly of the shrimp culture system. These results provide a basis for selectively regulating certain beneficial taxa to improve shrimp growth in culture systems.